Systematic review and meta-analysis of colistin plus meropenem therapy for the treatment of nosocomial pneumonia - Hazhir Moradi; Zahra Sadat Sajadi-Javan; Sarah Mousavi; Soodabeh Rostami; Bita Moradi Khaniabadi (Iranian Journal of Microbiology)
Background and Objectives: Nosocomial pneumonia caused by multidrug-resistant gram-negative bacteria presents a significant challenge for healthcare systems, as there are limited effective treatments available. This systematic review and meta-analysis aim to investigate the outcomes of colistin plus meropenem combination therapy on nosocomial pneumonia. Materials and Methods: An exhaustive search of PubMed, Scopus, Web of Science (WOS), and Embase databases was conducted, resulting in the extraction of 5 studies for qualitative assessment and meta-analysis. The study sample included 991 patients admitted with nosocomial pneumonia. The outcomes evaluated were clinical improvement, microbiological response, mortality, Sequential Organ Failure Assessment (SOFA) score, Acute Physiology and Chronic Health Evaluation (APACHE II) score, Charlson Comorbidity Index (CCI), Clinical Pulmonary Infection Score (CPIS), C-reactive protein (CRP) levels, procalcitonin (PCT) levels, and intensive care unit (ICU) duration. Results: The results demonstrated that colistin plus meropenem combination therapy significantly improved clinical outcomes (OR = 1.37, 95% CI = 1.04-1.81, p = 0.027), reduced SOFA scores (OR = -0.28, 95% CI = -0.44 to -0.11, p = 0.001), and increased CCI scores (OR = 0.16, 95% CI = 0.02-0.29, p = 0.021) compared to other medications. However, other evaluated parameters did not show significant differences. Conclusion: This meta-analysis indicates that colistin-meropenem combination therapy is superior to other colistin-based treatments for nosocomial pneumonia in terms of clinical improvement, SOFA score reduction, and CCI score increase. Nevertheless, other variables assessed did not exhibit remarkable differences between the treatment regimens.